The Impact of Different Intraoperative Fluid Administration Strategies on Postoperative Extubation Following Multilevel Thoracic and Lumbar Spine Surgery: A Propensity Score Matched Analysis. Issue 1 (30th May 2018) - Ramchandran, Subaraman; Day, Louis M; Line, Breton; Buckland, Aaron J; Passias, Peter; Protopsaltis, Themistocles; Bendo, John; Huncke, Tessa; Errico, Thomas J; Bess, Shay
Abstract: BACKGROUND: Patients undergoing multilevel spine surgery are at risk for delayed extubation. OBJECTIVE: To evaluate the impact of type and volume of intraoperative fluids administered during multilevel thoracic and/or lumbar spine surgery on postoperative extubation status. METHODS: Retrospective evaluation of medical records of patients ≥ 18 yr undergoing ≥ 4 levels of thoracic and/or lumbar spine fusions was performed. Patients were organized according to postoperative extubation status: immediate (IMEX; in OR/PACU) or delayed (DEX; outside OR/PACU). Propensity score matched (PSM) analysis was performed to compare IMEX and DEX groups. Volume, proportion, and ratios of intraoperative fluids administered were evaluated for the associated impact on extubation status. RESULTS: A total of 246 patients (198 IMEX, 48 DEX) were included. PSM analysis demonstrated that increased administration of non-cell saver blood products (NCSB) and increased ratio of crystalloid: colloids infused were independently associated with delayed extubation. With increasing EBL, IMEX had a proportionate reduction in crystalloid infusion (R = –0.5, P < .001), while the proportion of crystalloids infused remained relatively unchanged for DEX (R = –0.27; P = .06). Twenty-six percent of patients receiving crystalloid: colloid ratio > 3:1 had DEX compared to none of those receiving crystalloid: colloid ratio ≤ 3:1 ( P = .009). DEX had greater cardiac and pulmonary complications, surgical site infections and prolonged intensive care unit and hospital stay ( P < .05). CONCLUSION: PSM analysis of patients undergoing multilevel thoracic and/or lumbar spine fusion demonstrated that increased administration of crystalloid to colloid ratio is independently associated with delayed extubation. With increasing EBL, a proportionate reduction of crystalloids facilitates early extubation.